Strategic human resource management approaches for NPOs / Fathiah Nuraina Amaran @ Amran, Nurul Hidayana Mohd Noor and Aida Abdullah - Amaran @ Amran, Fathiah Nuraina; Mohd Noor, Nurul Hidayana; Abdullah, Aida (2021)
Non-profit organizations (NPOs) are a part of the non-profit sector, which is neither a business nor a government (Carroll, 2018). Its mission is to serve the public interest on the matters such as humanitarian, educational, scientific, cultural, or religious (Carroll, 2018). Ciucescu (2009) insisted NPOs as the voluntary parties established by citizens acting in their own free will to attain shared civic, economic, social, and cultural rights without generating a profit (Arapovic, Jahic, Halilbegovic, & Celebic, 2019). It has grown rapidly in number, size, and impact across the world where more the 10 million NPOs are established (Mohd Noor, 2017). On the other hand, strategic human resource management can be defined as the process of linking the human resource function with the organization's strategic objectives to improve its performance (Walk, Schinnenburg, & Handy, 2014). Strategic human resource management reflects the organization's resource-based perspective, which highlights the value of internal resources in gaining competitive advantages (Walk, Schinnenburg, & Handy, 2014). The competitive advantages can only be gained if the organisation has both human capital and human process aspects which collectively aligned (Walk, Schinnenburg, & Handy, 2014). The pressure for rationalisation has grown in NPOs as well so that employees are increasingly seen as a valuable resource and strategic human resource management as a critical instrument for organisational success (Eckardstein & Brandl, 2004). However, there are some weaknesses in the implementation of strategic human resource management among the NPOs. The lack of resources within NPOs such as competent human capital (Hasnan, Mohamad, Kamarudin, & Zainal Abidin, 2012). Individuals who are interested in doing charities but do not possess any qualifications and skills might harm the NPOs in some ways especially in terms of management. Plus, the employee's career development is also found to be weak which results in several problems such as recruitment, assignment, lay off, human resources development, and administration (Bromideh, 2011). Next, the lack of information on the employees’ perceptions (Walk, Schinnenburg, & Handy, 2014). They know little about how the employees perceive and how to evaluate human resource practices within the organization. The action of imitating the management system applied by the competitive for-profit sector organizations to adapt to the market changes also appeared to be one of the weaknesses (Walk, Schinnenburg, & Handy, 2014). Therefore, the researcher believes that the improvement on the implementation of strategic human resource management should be focused among the NPOs by referring to the approaches; administrative, strategic, motivational, and valued based. This study aims to investigate the influence of strategic human resource management that consists of four key approaches (i.e., administrative, strategic, motivational, and value-based) that will affect the effectiveness of Malaysian NPOs.